Mouse dendritic cells in the steady state: Hypoxia, autophagy, and stem cell factor. (7th September 2022) - Barroeta Seijas, Amairelys Belen; Simonetti, Sonia; Filippi, Irene; Naldini, Antonella; Favaretto, Gabriele; Colombo, Teresa; Natalini, Ambra; Antonangeli, Fabrizio; Laffranchi, Mattia; Sozzani, Silvano; Santoni, Angela; Di Rosa, Francesca
Abstract: Dendritic cells (DCs) are innate immune cells with a central role in immunity and tolerance. Under steady‐state, DCs are scattered in tissues as resting cells. Upon infection or injury, DCs get activated and acquire the full capacity to prime antigen‐specific CD4 + and CD8 + T cells, thus bridging innate and adaptive immunity. By secreting different sets of cytokines and chemokines, DCs orchestrate diverse types of immune responses, from a classical proinflammatory to an alternative pro‐repair one. DCs are highly heterogeneous, and physiological differences in tissue microenvironments greatly contribute to variations in DC phenotype. Oxygen tension is normally low in some lymphoid areas, including bone marrow (BM) hematopoietic niches; nevertheless, the possible impact of tissue hypoxia on DC physiology has been poorly investigated. We assessed whether DCs are hypoxic in BM and spleen, by staining for hypoxia‐inducible‐factor‐1α subunit (HIF‐1α), the master regulator of hypoxia‐induced response, and pimonidazole (PIM), a hypoxic marker, and by flow cytometric analysis. Indeed, we observed that mouse DCs have a hypoxic phenotype in spleen and BM, and showed some remarkable differences between DC subsets. Notably, DCs expressing membrane c‐kit, the receptor for stem cell factor (SCF), had a higher PIM median fluorescence intensity (MFI) than c‐kit − DCs, both in the spleen and in the BM. To determine whether SCF (a.k.a. kit ligand) has a role in DC hypoxia, we evaluated molecular pathways activated by SCF in c‐kit + BM‐derived DCs cultured in hypoxic conditions. Gene expression microarrays and gene set enrichment analysis supported the hypothesis that SCF had an impact on hypoxia response and inhibited autophagy‐related gene sets. Our results suggest that hypoxic response and autophagy, and their modulation by SCF, can play a role in DC homeostasis at the steady state, in agreement with our previous findings on SCF's role in DC survival. Significance statement: Dendritic cells (DCs) are key to immunity; nevertheless, their physiological homeostasis is only partially defined. We previously showed that stem cell factor (SCF) promotes DC survival and that its receptor c‐kit is variably expressed by the spleen and bone marrow (BM) DCs. Considering that some lymphoid niches have low oxygen tension, our aim was to evaluate whether: (i) DCs had a hypoxic phenotype; (ii) SCF could modulate hypoxia‐driven response in DCs. We found that mouse spleen and BM DCs, particularly those expressing c‐kit, had a hypoxic phenotype. In the presence of SCF, hypoxia‐induced response and autophagy, two processes that are central to cellular homeostasis, were modulated. Our results pave the way for the possibility to tune DC homeostasis by targeting SCF/c‐kit.